Anthraquinone‐Modified Silica Nanoparticles as Heterogeneous Photocatalyst for the Oxidative Hydroxylation of Arylboronic Acids - Martin, Maria Guadalupe (2023)
In this work, the synthesis and characterization of a heterogeneous photocatalyst based on spherical silica nanoparticles superficially modified with anthraquinone 2-carboxylic acid (AQ−COOH) are presented. The nanomaterial was characterized by TEM, SEM, FT-IR, diffuse reflectance, fluorescence, NMR, DLS, XRD and XPS. These analyses confirm the covalent linking of AQ−COOH with the NH2 functionality in the nanomaterial and, more importantly, the photocatalyst retains its photophysical properties once bound. The heterogeneous photocatalyst was successfully employed in the aerobic hydroxylation of arylboronic acids to phenols under sustainable reaction conditions. Phenols were obtained in high yields (up to 100 %) with low catalyst loading (3.5 mol %), reaching TOF values of 3.7 h−1. Using 2-propanol as solvent at room temperature, the visible light photocatalysis produced H2O2 as a key intermediate to promote the aerobic hydroxylation of arylboronic acids. The heterogeneous photocatalyst was reused at least 5 times, without modification of the nanomaterial structure and morphology. This simple heterogeneous system showed great catalytic activity under sustainable reaction conditions.